An Investigation of the Psychometric Properties of the Early Identification System–Student Report. (July 2019) - Huang, Francis L.; Reinke, Wendy M.; Thompson, Aaron; Herman, Keith C.; ,
An identified barrier to the widespread adoption of universal socioemotional and behavioral screening in schools may be that existing instruments may be too burdensome or costly to administer. As a result, the County Schools Mental Health Coalition came together to develop a common assessment system, the Early Identification System (EIS). The purpose of this study was to evaluate the psychometric properties of the EIS-student report, using a sample of third- to eighth-grade students. A series of exploratory and confirmatory factor analytic models were used with one exploratory ( n 1 = 450) and two holdout samples ( n 2 = 450, n 3 = 940). A six correlated factor model was supported showing adequate model fit, reliability (range = .73-.90), and convergent validity. Results suggest that the EIS is a promising, cost-free, and quick-to-administer universal screening tool that may assist educators and school psychologists identify students at risk of future socioemotional and behavioral difficulties.